Self-supporting SiC / SnO2 heterojunction nano array, preparation method thereof and application of self-supporting SiC / SnO2 heterojunction nano array in ultraviolet photoelectric detector

By forming SiC/SnO2 heterojunction nanoarrays on SiC materials, the problems of slow photoresponse and large dark current of pure SiC materials in PEC UV PD are solved, efficient UV light absorption and charge separation are achieved, and the optoelectronics are significantly improved. Detector performance and stability.

CN119364913APending Publication Date: 2025-01-24NINGBO UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313637.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the prior art, pure SiC materials, as photoanodes, have problems with slow light response and large dark current in PEC UV PD, making it difficult to achieve efficient and reliable photoelectrochemical reactions in complex underwater environments.

Method used

Self-supporting SiC/SnO2 heterojunction nanoarrays are used, prepared by anodization and chemical bath deposition methods to form SnO2 nanoparticles loaded on SiC single crystal nanowires, which improves the light absorption efficiency and charge separation transmission efficiency of the material.

Benefits of technology

It achieves efficient absorption of ultraviolet rays in the wavelength range of 200-400nm, significantly increases the photocurrent intensity, improves the overall performance of the detector, and maintains high sensitivity and long-term stability in complex underwater environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364913A_ABST
    Figure CN119364913A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ultraviolet photoelectric detection, and relates to a self-supporting SiC / SnO2 heterojunction nano array, a preparation method thereof and application of the self-supporting SiC / SnO2 heterojunction nano array in an ultraviolet photoelectric detector. The self-supporting SiC / SnO2 heterojunction nano array is prepared by adopting an anodic oxidation method and a chemical bath deposition method, and the method is simple and convenient in process and low in cost, and provides feasibility for large-scale production. The SiC / SnO2 heterojunction nano array has high-efficiency absorption capacity on ultraviolet rays within the wavelength range of 200-400 nanometers, and particularly achieves the maximization of light energy conversion efficiency at the wavelength of 260 nanometers, which means that the material can effectively capture and convert the ultraviolet rays, and a solid foundation is provided for a high-performance ultraviolet photoelectric detector.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultraviolet photoelectric detection, and relates to a self-supporting SiC / SnO2 heterojunction nanoarray and a preparation method thereof, and an application in an ultraviolet photoelectric detector. Background Art

[0002] As an important research tool for the underwater industry, underwater wireless communication technology plays a vital role in underwater exploration and maritime military. Among them, underwater optical communication technology stands out among many underwater communication methods due to its advantages such as high transmission rate, large bandwidth, high security, low latency and low cost, and is regarded as the future development direction of underwater wireless communication technology. In order to build an underwater optical communication system with more powerful communication capabilities, it is necessary to develop self-powered, water-resistant photodetectors (PDs) that can work stably and for a long time in harsh underwater environments.

[0003] Currently, the research and development of self-powered PDs is a hot area, and among the many self-powered PDs, photoelectrochemical (PEC) PDs have become the research focus in this field due to their high adjustability of light response, durable working ability under underwater conditions, cost-effectiveness, and manufacturing process without complex photolithography. Therefore, PEC PDs are considered to be an ideal choice in underwater optical communication systems, as they can not only provide reliable light receiving function, but also perform well in energy efficiency.

[0004] Among many wide bandgap semiconductor materials, 4H-SiC, as a typical third-generation semiconductor material, is recognized as one of the ideal choices for ultraviolet (UV) PD due to its wide bandgap, high carrier mobility, excellent physical and chemical stability, and unique photoelectric properties. Although a large number of studies have focused on the traditional UV PD applications of SiC nanomaterials and confirmed their excellent light detection performance, there are relatively few studies on PEC UV PD based on SiC nanomaterials. Especially in complex underwater environments, there are almost no reports on PEC PDs applicable to all scenarios. The main reasons for this situation are two aspects: First, the charge transfer process between semiconductors and electrolyte solutions in PEC UV PD places high demands on photoanode materials. Usually, one-dimensional nanostructured semiconductor materials are required to provide more charge transfer sites and accelerate ion migration, thereby achieving fast and efficient photoelectric conversion. Secondly, due to the limitations of its own photoelectrochemical properties, pure SiC is difficult to produce an effective photoelectrochemical effect with the electrolyte solution when used as a single photoanode material, resulting in a limited number of electron-hole pairs generated under illumination conditions, and its interface characteristics with the electrolyte solution are not conducive to the occurrence of efficient photoelectrochemical reactions. Therefore, the challenge in the future lies in how to improve the photoelectrochemical properties of SiC materials to make them more suitable for the application of PEC PD and ultimately achieve efficient and reliable operation in complex and harsh underwater environments in all scenarios. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the present invention aims to provide a self-supporting SiC / SnO2 heterojunction nanoarray, which realizes high-sensitivity detection of full-scenario underwater application environments, and effectively solves the problems of slow light response and high dark current of the array constructed of pure SiC as a photoanode.

[0006] One object of the present invention can be achieved by the following technical solutions:

[0007] A self-supporting SiC / SnO2 heterojunction nanoarray comprises SiC single crystal nanowires and SnO2 loaded on the SiC single crystal nanowires.

[0008] The present invention also provides a method for preparing the above self-supporting SiC / SnO2 heterojunction nanoarray, characterized in that the method comprises the following steps:

[0009] S1, placing SiC in an electrolyte for anodization to obtain SiC single crystal nanowires;

[0010] S2. Then, the SiC single crystal nanowire is placed in a Sn source solution for oil bath, and then annealed to obtain a self-supporting SiC / SnO2 heterojunction nanoarray.

[0011] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the electrolyte in step S1 is a mixture of C2H5OH, HF and H2O2 in a volume ratio of (5-8):(2-5):1.

[0012] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, step S1 anodization specifically includes the following steps: first anodize at 15-20V for 0.5-2min, with a cycle of 0.6-1.0ms (T on =0.3-0.5ms, T off =0.3-0.5ms), then anodize at 25-35V for 100-200s, and finally anodize at 15-20V for 8-12min. In the process of preparing SiC / SnO2 heterojunction nanoarrays of the present invention, the anodization step is a very critical link. If the anodization time is too short, it is not enough to form the required nanowire array structure on the surface of the SiC wafer. This structure is crucial to improving the light absorption capacity of the material because it can greatly increase the contact area between light and the material, thereby improving the light absorption efficiency. Without a suitable nanoarray structure, the light absorption capacity of the material will be limited, which directly affects the photoelectric performance of the final device. On the other hand, if the anodization time is too long, it will cause the oxide layer to be too deep, that is, the oxidation depth is too large. In this case, the distance that the carriers travel from the inside of the material to the surface increases, which may cause the carriers to recombine before reaching the surface, that is, the electrons and holes recombine, releasing energy without participating in the photoelectric conversion process. The recombination of carriers reduces the number of carriers that effectively participate in photoelectric conversion, thereby reducing the overall performance of the photodetector. Therefore, controlling the appropriate anodization time is one of the key factors in preparing high-performance SiC / SnO2 heterojunction nanoarrays. The correct oxidation time can ensure the formation of the best nanowire array structure, which can not only improve the light absorption efficiency of the material, but also avoid the carrier recombination problem caused by too deep an oxide layer, thereby ensuring the optoelectronic performance of the final device.

[0013] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the number of anodizations is 2-5 times. When the number of anodizations is set to 2-5 times, an ideal nanowire array structure can be formed on a SiC substrate. These nanowires not only have high density and uniformity, but also provide a good foundation for the subsequent deposition of SnO2, thereby promoting the formation of high-quality heterojunctions. However, if the number of anodizations exceeds 5 times, the nanowire array will be too deep, that is, the length of the nanowire is too long, which will bring two major problems: on the one hand, the overly long nanowire increases the transmission distance of the carrier from the bottom to the top of the nanowire, which not only prolongs the transmission time of the carrier, but also increases the probability of the carrier recombining during the transmission process, thereby reducing the photoelectric conversion efficiency; on the other hand, the overly deep nanowire structure may lead to the accumulation of internal stress in the material, affecting the structural stability of the nanowire, and thus affecting the performance of the entire device.

[0014] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the method for preparing a Sn source solution includes the following steps: uniformly mixing SnCl4·5H2O and water to obtain a mixed solution, and then dropping ammonia water into the mixed solution to obtain a Sn source solution.

[0015] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the molar ratio of SnCl4·5H2O and ammonia water is 1:(0.5-1.5). The present invention can achieve uniform deposition of SnO2 nanoparticles on the SiC nanowire array by precisely controlling the molar ratio of SnCl4·5H2O and ammonia water to 1:(0.5-1.5), thereby forming a high-quality heterojunction structure. SnO2 is uniformly distributed on the SiC nanowires, which can not only increase the surface area of ​​the material and improve the light absorption efficiency, but also enhance the separation and transmission efficiency of charges, which is crucial to the performance of photoelectrochemical ultraviolet photodetectors. In addition, this uniform distribution also helps to improve the passivation effect of the SiC nanowire surface, reduce surface defects, and thus improve the photoelectric conversion efficiency of the entire photodetector.

[0016] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the oil bath temperature in step S2 is 80-120°C and the time is 20-22h. The present invention ensures that SnO2 can be uniformly deposited on the SiC nanoarray by controlling the oil bath temperature and time to form an ideal heterojunction structure. If the oil bath temperature is set too high, it may cause violent boiling of the solution. This uncontrollable state not only increases the safety risk of the experimental operation, but also may cause the distribution of SnO2 particles on the SiC nanowires to become uneven, affecting the performance of the final product. In addition, too high a temperature may also cause structural changes in the material itself, such as SnO2 crystals growing too fast to form larger particles, which will destroy the uniformity of the nanoarray. On the contrary, if the oil bath temperature is set too low, the deposition process of SnO2 will become very slow, and may even cause the deposition process to stagnate due to reaction kinetics, so that SnO2 cannot be effectively deposited on the SiC nanoarray, which will directly lead to synthesis failure and the desired SiC / SnO2 heterojunction nanoarray cannot be obtained. Therefore, the present invention selects the appropriate oil bath temperature and time is the key to prepare high-quality SiC / SnO2 heterojunction nanoarrays. The appropriate temperature can ensure that SnO2 is uniformly deposited on the SiC nanoarray to form a uniform and stable heterojunction structure, thereby optimizing the performance of the photodetector. The appropriate time ensures that the reaction is fully carried out, which not only avoids incomplete deposition due to too short a time, but also prevents side reactions or material damage that may be caused by too long a time. In summary, reasonable temperature and time control are crucial to ensuring the quality of the material and the functional performance of the final device.

[0017] In the above-mentioned method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray, the annealing temperature of step S2 is 250-350°C. The present invention needs to control the annealing temperature to 250-350°C. If the annealing temperature is too low, the SnO2 precursor may not be completely converted into SnO2. This will cause the SnO2 nanoparticles to be unevenly distributed on the surface of the SiC nanowires, and even form a discontinuous film. This incomplete conversion will seriously affect the formation of the heterojunction, thereby reducing the photoelectric performance of the material. The incompletely converted SnO2 precursor may cause an increase in defects at the heterojunction interface, and these defects will become the center of carrier recombination, further reducing the photoelectric conversion efficiency. If the annealing temperature is too high, the material composition of the surface of the SiC nanowire may be destroyed, resulting in changes in the surface state, which will not only affect the structural integrity of the SiC nanowire, but also reduce its photoelectric performance. Excessive temperature may also cause the morphology of the SnO2 nanoparticles to change, such as particle growth or aggregation, which will reduce the contact area between SnO2 and the SiC nanowire, thereby affecting the performance of the heterojunction.

[0018] Preferably, the self-supporting SiC / SnO2 heterojunction nanoarray absorbs light sources with wavelengths in the range of 200-400 nm.

[0019] The present invention also provides a photoelectrochemical ultraviolet photodetector, which includes the above-mentioned self-supporting SiC / SnO2 heterojunction nanoarray or the self-supporting SiC / SnO2 heterojunction nanoarray prepared by the above-mentioned preparation method.

[0020] Preferably, the photoelectrochemical ultraviolet photodetector comprises:

[0021] The above-mentioned self-supporting SiC / SnO2 heterojunction nanoarray, Pt electrode and Ag / AgCl (saturated KCl solution) electrode, wherein the SiC / SnO2 heterojunction nanoarray material, Pt electrode and Ag / AgCl (saturated KCl solution) electrode are the working electrode, counter electrode and reference electrode respectively.

[0022] The present invention also provides a method for preparing the above-mentioned photoelectrochemical ultraviolet photodetector, which comprises the following steps: using the above-mentioned self-supporting SiC / SnO2 heterojunction nanoarray as a working electrode, a Pt electrode as a counter electrode, and an Ag / AgCl (saturated KCl solution) electrode as a reference electrode, and assembling them into a typical three-electrode system using an electrochemical workstation (CHI660D, Shanghai Chenhua Instrument Co., Ltd., China); an electrolyte solution is arranged in a reaction container, the above-mentioned self-supporting electrode is detachably arranged on the container cover, the three electrodes are immersed in the electrolyte solution, and the container cover is closed on the reaction container to form a SiC / SnO2-based photoelectrochemical ultraviolet photodetector.

[0023] In the above-mentioned photoelectrochemical ultraviolet photodetector, the ultraviolet photodetector is under a bias voltage of 0V and 27.1mW / cm 2 At low light power density, the photocurrent in low-latitude seawater solution can reach 654.2μA / cm 2 .

[0024] Preferably, when a bias voltage is applied and ultraviolet light is applied, the photocurrent of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector increases with the increase of light intensity.

[0025] Preferably, when a bias voltage is applied and ultraviolet light is applied, the photocurrent of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector increases with the increase of electrolyte concentration.

[0026] Preferably, when bias voltage is applied and ultraviolet light is applied, the photocurrent of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector is one order of magnitude higher than that of the pure SiC nanoarray-based photoelectrochemical ultraviolet photodetector.

[0027] Preferably, when bias voltage is applied and ultraviolet light is applied, in a seawater solution, the photocurrent of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector increases with the increase of the salinity of the seawater solution.

[0028] Preferably, at 27.1 mW / cm 2 Under low light power density, the light response time of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector is as low as 30ms.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The SiC / SnO2 heterojunction nanoarray of the present invention has a high efficiency in absorbing ultraviolet light in the wavelength range of 200-400 nanometers, and in particular, maximizes the light energy conversion efficiency at a wavelength of 260 nanometers, which means that the material can effectively capture and convert ultraviolet light, providing a solid foundation for high-performance ultraviolet photodetectors. The appropriate amount of defects at the heterojunction interface of the present invention not only prolongs the life of carriers, but also provides additional active sites, further promoting the generation of photocurrent, which is an important feature of the present invention.

[0031] 2. The photoelectrochemical ultraviolet photodetector prepared by the SiC / SnO2 heterojunction nanoarray of the present invention has significantly improved the photocurrent intensity by at least one order of magnitude compared to the traditional pure SiC nanoarray-based ultraviolet photodetector. This performance leap is mainly attributed to the built-in electric field formed on the heterojunction interface, which optimizes the carrier transmission path and greatly enhances the photocurrent, thereby improving the overall performance of the detector.

[0032] 3. The photoelectrochemical ultraviolet photodetector prepared by the SiC / SnO2 heterojunction nanoarray of the present invention exhibits excellent rapid response capability. At an optical power density as low as 27.1 milliwatts per square centimeter, the rise time and fall time of the detector are only 30 milliseconds and 120 milliseconds, respectively. This means that it can not only quickly detect changes in optical signals, but also recover very quickly, showing excellent time resolution.

[0033] 4. The photoelectrochemical ultraviolet photodetector prepared by the SiC / SnO2 heterojunction nanoarray of the present invention can maintain high sensitivity detection of ultraviolet light in seawater environments at different latitudes and in solutions with different pH values. In addition, it also exhibits long-term operational stability and anti-aging performance, ensuring reliable operation under various complex environmental conditions.

[0034] 5. The self-supporting SiC / SnO2 heterojunction nanoarray of the present invention is prepared by anodization and chemical bath deposition, which is not only simple in process but also low in cost, providing feasibility for large-scale production. This shows that ultraviolet photodetectors based on this material have broad application prospects in the future, especially in the field of underwater monitoring and detection that requires high sensitivity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the preparation process of the self-supporting SiC / SnO2 heterojunction nanoarray in Example 1 of the present invention.

[0036] Figure 2 This is a surface scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-19.5 heterojunction nanoarray prepared in Example 2 of the present invention at 200 nm.

[0037] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-19.5 heterojunction nanoarray prepared in Example 2 of the present invention at 2 μm.

[0038] Figure 4 This is a surface scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-21 heterojunction nanoarray prepared in Example 1 of the present invention at 200 nm.

[0039] Figure 5 This is a scanning electron microscope (SEM) image of the cross section at 2 μm of the self-supporting SiC / SnO2-21 heterojunction nanoarray prepared in Example 1 of the present invention.

[0040] Figure 6 This is a surface scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-22.5 heterojunction nanoarray prepared in Example 3 of the present invention at 2000 nm.

[0041] Figure 7 This is a cross-sectional scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-22.5 heterojunction nanoarray prepared in Example 3 of the present invention at 2 μm.

[0042] Figure 8 This is an X-ray diffraction (XRD) pattern of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0043] Fig. 9 This is an X-ray photoelectron spectroscopy (XPS) graph of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0044] Fig.10This is a high-resolution spectrum of Si 2p of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0045] Fig.11 This is a high-resolution spectrum of C1s of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0046] Fig.12 This is a high-resolution spectrum of Sn 3d of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0047] Fig.13 This is a high-resolution spectrum of O1s of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0048] Fig.14 1 is the energy band diagram of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0049] Fig.15 This is an ultraviolet-visible (UV-Vis) absorption spectrum of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention.

[0050] Fig.16 The current-time (It) response curves of the self-supporting SiC / SnO2-based photoelectrochemical ultraviolet photodetector at different reaction times prepared in Example 1 of the present invention in a low-latitude seawater solution, with a 0V bias voltage applied and ultraviolet light irradiation.

[0051] Fig.17 The current-time (It) response curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 of Test 1 of the present invention and the pure SiC nanoarray-based photoelectrochemical ultraviolet photodetector in Comparative Example 1 after applying a 0V bias voltage and ultraviolet light irradiation in a low-latitude seawater solution.

[0052] Fig.18 Current-light power density curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 and the pure SiC nanoarray-based photoelectrochemical ultraviolet photodetector in Comparative Example 1 in low-latitude seawater solution after applying a 0V bias voltage and ultraviolet light irradiation.

[0053] Fig.19The response rates (R) of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 and the pure SiC nanowire array-based photoelectrochemical ultraviolet photodetector in Comparative Example 1 under different light power densities in low-latitude seawater solution after applying a 0V bias voltage and ultraviolet light irradiation are shown in Figure 1. λ )curve.

[0054] Fig. 20 The detection rate (D) of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 of the present invention and the pure SiC nanowire array-based photoelectrochemical ultraviolet photodetector in Comparative Example 1 in low-latitude seawater solution is 0V biased and irradiated with ultraviolet light at different light power densities. * )curve.

[0055] Fig.21 External quantum efficiency (EQE) curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 of Test 1 of the present invention and the pure SiC nanowire array-based photoelectrochemical ultraviolet photodetector in Comparative Example 1 at different light power densities after applying a 0V bias voltage and ultraviolet light irradiation in a low-latitude seawater solution.

[0056] Fig. 22 It is the rise time of transient current measured by the SiC-based photoelectrochemical ultraviolet photodetector prepared by comparative example 1 in test 1 of the present invention in a low-latitude seawater solution.

[0057] Fig.23 It is the drop time of transient current measured by the SiC-based photoelectrochemical ultraviolet photodetector prepared by comparative example 1 in test 1 of the present invention in a low-latitude seawater solution.

[0058] Fig.24 It is the rise time of transient current measured by the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 1 of the present invention in a low-latitude seawater solution.

[0059] Fig.25 It is the falling time of transient current measured by the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 1 of the present invention in a low-latitude seawater solution.

[0060] Fig.26 This is a diagram of the self-powered energy band mechanism of the self-supporting SiC / SnO2 heterojunction nanoarray material in Test 1 of the present invention.

[0061] Fig. 27 These are the specific parameters of seawater when tested in seawater solutions at different latitudes.

[0062] Fig.28 The current-time (It) response curve of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 2 of the present invention in a low-latitude seawater solution with a 0V bias voltage applied and ultraviolet light irradiation.

[0063] Fig.29 The current-time (It) response curve of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 2 of the present invention in a mid-latitude seawater solution with a 0V bias voltage applied and ultraviolet light irradiation.

[0064] Fig.30 The current-time (It) response curve of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 2 of the present invention in a high-latitude seawater solution with a 0V bias voltage applied and ultraviolet light irradiation.

[0065] Fig.31 They are respectively the stability test curves of a fresh self-supporting SiC / SnO2 heterojunction nanoarray material-based photoelectrochemical ultraviolet photodetector prepared in Application Example 1 of the present invention and a SiC / SnO2 heterojunction material-based photoelectrochemical ultraviolet photodetector stored for one month in a low-latitude seawater solution, with 0 bias voltage applied and ultraviolet light irradiation for 3000s.

[0066] Fig.32 The current-time (It) response curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 3 of the present invention at different temperatures after applying a 0V bias voltage and ultraviolet light irradiation in a 0.5 mol / L H2SO4 solution.

[0067] Fig.33 The current-time (It) response curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 3 of the present invention at different temperatures after applying a 0V bias voltage and ultraviolet light irradiation in a 0.5mol / L Na2SO4 solution.

[0068] Fig.34 The current-time (It) response curves of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 in Test 3 of the present invention at different temperatures in a 0.5 mol / L KOH solution with a 0V bias voltage applied and ultraviolet light irradiation. DETAILED DESCRIPTION

[0069] The technical scheme of the present invention is further described below by specific embodiments in conjunction with the accompanying drawings. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0070] Embodiment 1:

[0071] S1. Preparation of SiC / SnO2 heterojunction materials: The preparation flow chart is as follows Figure 1 As shown in Figure 2, the preparation of 4H-SiC nanowire arrays is based on the anodization method. First, the SiC sheet and the graphite plate are used as the anode and cathode, respectively. In a C2H5OH:HF:H2O2 electrolyte with a volume ratio of 6:3:1, the SiC sheet is anodized for 1 min at 17 V using a pulse power supply (SOYI-300-500-5M) with a cycle of 0.8 ms (T on =0.4ms, T off =0.4ms), so that a cap layer is formed on the top surface of the SiC sheet. Subsequently, the applied voltage is increased to 27V, with a duty cycle of 100%, for about 120 seconds, so that the previously formed cap layer is completely removed, and then anodized at 18V for 10min.

[0072] S2, performing a second anodization treatment in a C2H5OH:HF:H2O2 electrolyte having the same concentration volume ratio of 6:3:1 to obtain a single crystal integrated self-supporting SiC nanowire array, the anodization treatment is exactly the same as step S1;

[0073] S3, 2.4 mmol of SnCl4·5H2O and 2.4 mmol of aqueous ammonia were mixed in a glass beaker containing 60 ml of deionized water, and stirred for 5 min to obtain a solution;

[0074] S4. The anodized single crystal integrated self-supporting SiC nanowire array was placed into the mixed solution, then subjected to an oil bath at 90°C for 21 minutes, and then annealed at 300°C. Finally, it was washed with deionized water for 3 times and dried with nitrogen to obtain a self-supporting SiC / SnO2 heterojunction nanoarray.

[0075] The structure of the self-supporting SiC / SnO2 heterojunction nanoarray prepared above was characterized by scanning electron microscopy (FESEM, S-4800, Hitachi, Japan). Figure 4-5 As shown in Figure 2, it can be seen that after chemical bath deposition, the SnO2 film grows on the surface of the SiC nanoarray, forming the desired SiC / SnO2 heterojunction structure. This structure effectively passivates the surface of the SiC nanoarray, thereby reducing the defects on the surface of the SiC nanoarray and increasing the active sites for the PEC reaction.

[0076] The elemental analysis of the self-supporting SiC / SnO2 heterojunction nanoarray prepared above was performed using an X-ray photoelectron spectroscopy analyzer (XPS, Thermo Scientific K-Alpha). The XPS graph is shown in FIG. Figure 9-13 As shown, the results confirm that the SiCSnO2 heterojunction sample is composed of four elements: Si, C, Sn, and O, which is consistent with the expected composition of the composite material.

[0077] X-ray diffraction was used to characterize the structure of the prepared self-supporting SiC / SnO2 heterojunction nanoarray. Figure 8 As shown in the figure, it is not difficult to see that the relevant diffraction peaks of 4H-SiC and SnO2 appear simultaneously in the spectrum of SiC / SnO2 heterojunction material, confirming the coexistence of SnO2 and 4H-SiC in the composite material. The absence of any additional impurity peaks further confirms the high purity of the synthesized product.

[0078] Fig.14 This is the energy band diagram of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 of the present invention. As can be seen from the figure, the two materials form a type II heterojunction, and electrons and holes are transferred to SiC and SnO2 respectively, so that a potential difference is formed between the two materials, which promotes the separation of carriers and enhances the photoelectric performance.

[0079] The absorption characteristics of the prepared self-supporting SiC / SnO2 heterojunction nanoarrays in the UV-Vis wavelength range were measured using UV-vis absorption spectroscopy (UV-vis, U-3900, Hitachi, Japan). Fig.15 As shown, it can be seen that the SiC / SnO2 heterojunction material exhibits a high absorption characteristic for ultraviolet light with a wavelength below 400nm.

[0080] Embodiment 2:

[0081] S1. Preparation of SiC / SnO2 heterojunction materials: Preparation of 4H-SiC nanowire arrays Based on the anodization method, SiC sheets and graphite plates were used as anodes and cathodes, respectively. In a C2H5OH:HF:H2O2 electrolyte with a volume ratio of 6:3:1, a pulse power supply (SOYI-300-500-5M) was used to anodize the SiC sheets at 17 V for 1 minute with a cycle of 0.8 ms (T on =0.4ms, T off =0.4ms), so that a cap layer is formed on the top surface of the SiC sheet. Subsequently, the applied voltage is increased to 27V, with a duty cycle of 100%, for about 120 seconds, so that the previously formed cap layer is completely removed, and then anodized at 18V for 10min.

[0082] S2, performing a second anodization treatment in a C2H5OH:HF:H2O2 electrolyte having the same concentration volume ratio of 6:3:1 to obtain a single crystal integrated self-supporting SiC nanowire array, the anodization treatment is exactly the same as step S1;

[0083] S3, 2.4 mmol of SnCl4·5H2O and 2.4 mmol of aqueous ammonia were mixed in a glass beaker containing 60 ml of deionized water, and stirred for 5 min to obtain a solution;

[0084] S4. The anodized single crystal integrated self-supporting SiC nanowire array was placed into the mixed solution, and then subjected to an oil bath at 90°C for 19.5h, and then annealed at 300°C. Finally, it was washed with deionized water for 3 times and dried with nitrogen to obtain a self-supporting SiC / SnO2 heterojunction nanoarray.

[0085] Figure 2 This is a surface scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-19.5 heterojunction nanoarray at 200 nm prepared in Example 2 of the present invention. As can be seen from the figure, the SnO2 distribution on the surface of the sample after 19.5 hours of reaction is not uniform, which will lead to more defects on the surface of the material, increase the probability of carrier recombination, and reduce the photoelectric performance.

[0086] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-19.5 heterojunction nanoarray prepared in Example 2 of the present invention at 2 μm. As can be seen from the image, the thickness of SnO2 in the sample reacted for 19.5 hours is 2.1 μm.

[0087] Embodiment 3:

[0088] S1. Preparation of SiC / SnO2 heterojunction materials: Preparation of 4H-SiC nanowire arrays Based on the anodization method, SiC sheets and graphite plates were used as anodes and cathodes, respectively. In a C2H5OH:HF:H2O2 electrolyte with a volume ratio of 6:3:1, a pulse power supply (SOYI-300-500-5M) was used to anodize the SiC sheets at 17 V for 1 minute with a cycle of 0.8 ms (T on =0.4ms, T off =0.4ms), so that a cap layer is formed on the top surface of the SiC sheet. Subsequently, the applied voltage is increased to 27V, with a duty cycle of 100%, for about 120 seconds, so that the previously formed cap layer is completely removed, and then anodized at 18V for 10min.

[0089] S2, performing a second anodization treatment in a C2H5OH:HF:H2O2 electrolyte having the same concentration volume ratio of 6:3:1 to obtain a single crystal integrated self-supporting SiC nanowire array, the anodization treatment is exactly the same as step S1;

[0090] S3, 2.4 mmol of SnCl4·5H2O and 2.4 mmol of aqueous ammonia were mixed in a glass beaker containing 60 ml of deionized water, and stirred for 5 min to obtain a solution;

[0091] S4. The anodized single crystal integrated self-supporting SiC nanowire array is placed in a mixed solution, then subjected to an oil bath at 90°C for 22.5h, and then annealed at 300°C. Finally, it is washed with deionized water for 3 times and dried with nitrogen to obtain a self-supporting SiC / SnO2 heterojunction nanoarray.

[0092] Figure 6 This is a surface scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-22.5 heterojunction nanoarray at 2000 nm prepared in Example 3 of the present invention. It can be seen from the figure that SnO2 is evenly distributed on the surface of the sample that has been reacted for 22.5 hours.

[0093] Figure 7 This is a cross-sectional scanning electron microscope (SEM) image of the self-supporting SiC / SnO2-22.5 heterojunction nanoarray prepared in Example 3 of the present invention at 2 μm. It can be seen from the figure that the thickness of SnO2 in the sample after 22.5 hours of reaction is 5.2 μm. Too thick a SnO2 layer will increase the resistance, thereby reducing the photoelectric performance.

[0094] Comparative Example 1:

[0095] The only difference from Example 1 is that in Comparative Example 1, the SiC nanowire array is not subjected to chemical bath deposition.

[0096] Comparative Example 2:

[0097] The only difference from Example 1 is that in Comparative Example 2, SiC is not subjected to anodization treatment.

[0098] Comparative Example 3:

[0099] The only difference from Example 1 is that the number of times of anodization is once.

[0100] Application Example 1:

[0101] S1. The self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 was directly used as the working electrode, the Pt electrode was the counter electrode, and the Ag / AgCl (saturated KCl solution) electrode was the reference electrode, and assembled into a typical three-electrode system using an electrochemical workstation (CHI660D, Chenhua Instrument Co., Ltd., Shanghai, China).

[0102] S2. The electrolyte solution is arranged in the reaction container. The three-electrode system is detachably arranged on the container cover. The three electrodes are immersed in the electrolyte solution. The container cover is closed with the reaction container to form a SiC / SnO2-based photoelectrochemical ultraviolet photodetector. A light-transmitting window is fixedly arranged on the side wall of the reaction container for transmitting light.

[0103] Fig.26 This is a self-powered energy band mechanism diagram of the self-supporting SiC / SnO2 heterojunction nanoarray material in Test 1 of the present invention. As can be seen from the figure, when light irradiates the surface of the material, the material generates photogenerated carriers. Because of the type II band structure, holes are transferred to the SnO2 surface to participate in the oxygen evolution reaction, and electrons are transferred to SiC and transmitted to the cathode through the nanowires and the unanodized SiC part, and finally participate in the hydrogen evolution reaction.

[0104] Fig. 27 The specific parameters of seawater when the present invention is tested in seawater solutions at different latitudes. As can be seen from the figure, the parameters of seawater used in the test are salinity 3.6‰, temperature 30°C; salinity 3.3%0, temperature 15°C; salinity 3.0‰, temperature 5°C. These three data represent the parameters of seawater at three different latitude levels.

[0105] Test 1: When the electrolyte solution is a low-latitude seawater solution, the performance of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector in Application Example 1 is tested by applying a 0V bias voltage and 375nm light irradiation in sequence.

[0106] Fig.16 The current-time (It) response curves of the self-supporting SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Examples 1-3 of the present invention at different reaction times in low-latitude seawater solution, with 0V bias voltage applied and ultraviolet light irradiation. As can be seen from the figure, the performance of the material first increases and then decreases with the increase of reaction time, and the performance is the highest when the reaction time reaches 21h.

[0107] Fig.17 Pure SiC and the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 were directly used as photoanodes, and the photoelectric properties of the two were studied in low-latitude seawater solutions and at light power densities of 1.7-27.1 mW / cm 2 The results show that the photocurrent of the self-supporting SiC / SnO2 heterojunction nanoarray is one order of magnitude higher than that of the pure SiC nanowire array, and the photocurrent value can reach 654.2μA / cm 2 The increase in photocurrent is mainly due to the formation of the heterojunction interface.

[0108] Fig.18 The photocurrent curves of the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Example 1 at different light power densities in Na2SO4 solution show that the photocurrent gradually increases with the increase of light power density. The specific data are shown in Table 1 below:

[0109] Table 1: Photocurrent data at different optical power densities

[0110]

[0111] Figure 19-21 They are the response rates (R λ ), detection rate (D * ) and external quantum efficiency (EQE), it can be found that when the optical power density is fixed at level I, the SiC / SnO2-based photoelectrochemical ultraviolet photodetector shows excellent performance, and its R λ The value reaches 1980mA / W, D * The value can reach 1.98×10 11 The Jones,EQE value is 65.48%. The results show that the photodetector of Example 1 performs well in a low light power density environment. This is of great significance for application scenarios that require high sensitivity and high efficiency (such as nighttime monitoring in a low light environment).

[0112] Figure 24-25 The rise time and decay time of transient current of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector prepared in Example 1 are changed in low-latitude seawater solution. The millisecond response rate indicates that the SiC / SnO2-based photoelectrochemical ultraviolet photodetector has a rapid light response. This excellent performance is attributed to the structural characteristics of the SiC / SnO2 heterojunction. The formation of the SiC / SnO2 heterojunction introduces a new band structure and interface effect, which helps to absorb photons and separate carriers more efficiently. Due to the presence of the heterojunction, the photoexcited carriers can be separated and collected more quickly, thereby achieving a rapid response of the photodetector.

[0113] Fig.31 The long-term photocurrent-time response curve of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector freshly prepared and stored for one month in Example 1 is shown in the low-latitude seawater solution. It can be seen that the SiC / SnO2-based photoelectrochemical ultraviolet photodetector in Example 1 has good long-term stability and good anti-aging stability in the low-latitude seawater solution within 3000 s.

[0114] Test 2: The electrolyte solution is a low-latitude, mid-latitude, and high-latitude seawater solution. The SiC / SnO2-based photoelectrochemical ultraviolet photodetector in Application Example 1 is placed therein, and a 0 bias voltage and 375nm light irradiation are applied in turn to perform performance tests.

[0115] Figure 28-30 The photocurrent curves of the SiC / SnO2-based photoelectrochemical UV photodetector in Application Example 1 at different light power densities in seawater solutions of different concentrations and temperatures are shown. The light response of the SiC / SnO2-based PEC UV PD decreases significantly with the decrease in the concentration of the seawater solution, showing the high sensitivity of the device to the solution concentration. These sensitivities mainly come from the fact that the concentration and migration ability of ions in the solution greatly affect the size of the photocurrent. When the ion concentration in the solution is low, less charge is generated on the surface of the photoelectrode, resulting in less charge migration and smaller photocurrent.

[0116] Test 3: The electrolyte solution is 0.5 mol / L Na2SO4, H2SO4, KOH solution, and the SiC / SnO2-based photoelectrochemical ultraviolet photodetector in Example 2 is placed therein, and the performance is tested under self-powered conditions and 375 nm light irradiation.

[0117] Figure 32-34 The self-powered photocurrent curves of the SiC / SnO2-based photoelectrochemical UV photodetector in the application example 1 under different light power densities in solutions with different pH values. It can be seen that even under different acid and alkaline conditions, the SiC / SnO2-based PEC UV PD still has good light response performance. Its maximum photocurrent can reach 634μA / cm 2 This is because Fig.18 As shown in the figure, since SnO2 and SiC have different lattice structures and energy band structures, a heterojunction interface is formed at the contact. When the SiC / SnO2 heterojunction interface is formed, charge transfer occurs due to the difference in electron affinity and bandgap width between the two materials, resulting in the formation of a built-in electric field near the interface. This built-in electric field helps to separate photogenerated electrons and holes. At the same time, the separated electrons and holes move to the platinum electrode and the SiC / SnO2 electrode respectively, and participate in the redox reaction at the electrolyte interface to generate H2 and O2, ultimately completing the charge exchange of the entire circuit.

[0118] Application Comparative Example 1:

[0119] The only difference from Application Example 1 is that the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Comparative Example 1 is directly used as a working electrode.

[0120] Figure 22-23The current-time (It) response curve after applying a 0V bias voltage and ultraviolet light irradiation in a low-latitude seawater solution. It can be clearly observed that the photocurrent of the SiC / SnO2 heterojunction nanoarray prepared in Example 1 is 1 order of magnitude higher than that of the SiC nanowire array prepared in Comparative Example 1. The increase in photocurrent is mainly due to the formation of the heterojunction interface. First, the formation of the heterojunction interface leads to an enhanced charge separation effect. In the SiC / SnO2 heterojunction material, due to the different electron affinities and energy gap sizes of the two materials, an energy level shift is formed at the interface after light excitation, thereby forming a coupling region of electrons and holes. This coupling region makes the separation of photogenerated carriers more efficient. Secondly, the heterojunction changes the transport and diffusion characteristics of carriers in the material. The formation of the SiC / SnO2 heterojunction increases the mobility and diffusion length of carriers in the material, thereby increasing the collection efficiency of photogenerated carriers. At the same time, the formation of SiC / SnO2 heterojunction leads to the enhancement of the surface reaction activity of the material, changes the chemical properties of the material surface, and improves the surface light absorption and photoelectric conversion efficiency. Some additional interface states will also be formed on the heterojunction interface. These interface states have an important influence on the transport and recombination of carriers, which can further improve the efficiency of photocurrent generation. The synergistic effect of these factors enables SiC / SnO2 heterojunction materials to generate photogenerated carriers more efficiently, which undoubtedly shows that heterojunction materials have a significant enhancement effect in photocurrent generation.

[0121] Application Comparative Example 2:

[0122] The only difference from Application Example 1 is that the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Comparative Example 2 is directly used as a working electrode.

[0123] SiC wafers that have not undergone the anodization process cannot form a nano-array structure on their surface, which greatly reduces their light absorption capacity compared to SiC wafers that have formed an array structure, ultimately resulting in poor photoelectric performance.

[0124] Application Comparative Example 3:

[0125] The only difference from Application Example 1 is that the self-supporting SiC / SnO2 heterojunction nanoarray prepared in Comparative Example 3 is directly used as a working electrode.

[0126] SiC wafers that have not undergone secondary anodization cannot form a complete nanowire array structure because the total anodization time is short, resulting in a lower light absorption capacity than SiC wafers that have formed a complete array structure, ultimately leading to poor photoelectric performance.

[0127] In summary, the SiC / SnO2-based photoelectrochemical ultraviolet photodetector of the present invention has excellent light response capability, which is one order of magnitude higher than the photocurrent of the pure SiC nanowire array-based photoelectrochemical ultraviolet photodetector, and has high sensitivity to solution concentration; it has fast response capability; it has excellent long-term operation stability and good anti-aging stability in seawater solution; it exhibits excellent sensitivity to light signals, detector response capability and input light signal capture capability at low light power density. In addition, the synthesis method of SiC / SnO2 heterojunction material is simple, the production cost is low, and large-scale production can be achieved. The improvement of the SiC / SnO2-based photoelectrochemical ultraviolet photodetector of the present invention is mainly attributed to the effective synergistic effect of the heterojunction interface effect, cutoff wavelength and interface defects of the SiC / SnO2 heterojunction material.

[0128] The parts of the embodiments herein that are not exhaustive of the midpoint values ​​of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.

[0129] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.

[0130] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A self-supporting SiC / SnO2 heterojunction nanoarray, characterized in that: The nanoarray includes SiC single crystal nanowires and SnO2 loaded on the SiC single crystal nanowires.

2. A method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray as claimed in claim 1, characterized in that: The method comprises the following steps: S1, placing SiC in an electrolyte for anodization to obtain SiC single crystal nanowires; S2. Then, the SiC single crystal nanowire is placed in a Sn source solution for oil bath, and then annealed to obtain a self-supporting SiC / SnO2 heterojunction nanoarray.

3. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: The electrolyte in step S1 is a mixture of C2H5OH, HF and H2O2 in a volume ratio of (5-8):(2-5):

1.

4. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: Step S1 anodization specifically includes the following steps: first anodize at 15-20V for 0.5-2min, with a cycle of 0.6-1.0ms (T on =0.3-0.5ms, T off =0.3-0.5 ms), then anodized at 25-35 V for 100-200 s, and finally anodized at 15-20 V for 8-12 min.

5. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: The number of anodization in step S1 is 2-5 times.

6. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: The Sn source solution preparation method comprises the following steps: uniformly mixing SnCl4·5H2O and water to obtain a mixed solution, and then dropping ammonia water into the mixed solution to obtain a Sn source solution.

7. A method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 6, characterized in that: The molar ratio of SnCl4·5H2O to aqueous ammonia is 1:(0.5-1.5).

8. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: In step S2, the oil bath temperature is 80-120° C. and the time is 20-22 h.

9. The method for preparing a self-supporting SiC / SnO2 heterojunction nanoarray according to claim 2, characterized in that: The annealing temperature in step S2 is 250-350°C.

10. A photoelectrochemical ultraviolet photodetector, characterized in that: The photoelectrochemical ultraviolet photodetector comprises the self-supporting SiC / SnO2 heterojunction nanoarray described in claim 1 or the self-supporting SiC / SnO2 heterojunction nanoarray prepared by the preparation method described in claims 2-9.